Effect of Trigonella Foenum-Graecum seed powder on anthropometrical and nutritional parameter - Victoria KONOPELNYUK, Larysa KOT, Sándor MAKAI, Ludmila OSTAPCHENKO (Journal of Applied Pharmaceutical Science, 2015)
The purpose of this study was to assess effect of powder from Trigonella foenum-graecum seed anthropometrical and nutritional parameters of obese rats. This study was carried out on rats with initial weighing of 155-185 g. Rats of the control group have been fed with a standard food and water for 14 weeks. Rats of the experimental groups have been fed by a high-caloric diet for 14 weeks and fed by a standard chow which containing: fenugreek (2%.) During the research it was determined the main indicators of obesity such as body weight, food intake, body mass index, specific rate of body mass gain, energy intake, feed efficiency et al. Studies have shown that the addition of 2% powder from Trigonella foenum-graecum seed in food promoted weight loss and other anthropometrical and nutritional parameters.
Keywords: Obesity, fenugreek, body weight, food intake.